Spectrum of Glomerular Diseases in Biopsy Proven Nephrotic Syndrome in Adults in Tertiary Center of Nepal - Shrestha, Dineshowri; Agrawal, Rajendra Kumar; Hada, Rajani; Baral, Anil (Journal of National Heart and Lung Society Nepal, 2024)
Background: Glomerulonephritis (GN) is the important cause of chronic renal disease and had been reported as first common cause of CKD in Nepal after Diabetes and Hypertension. Correct diagnosis of glomerulonephritis requires renal biopsy and correlation with clinical and biochemical parameters. Methods: This was an observational study conducted in Department of Nephrology, Bir Hospital Kathmandu, during the period of one year. A total of 88 patients were enrolled. Nephrotic syndrome was established by a detailed history, physical examination and investigations including kidney biopsy.. Results: Among the enrolled patients.51.2% were male and 48.8% were female. Almost all patients had hyperlipidemia. IgA Nephropathy was found to be the first commonest cause in 22.8% , second Lupus Nephritis in 9.3%, third Focal Segmental Glomerulosclerosis (FSGS) in 18.2% fourth was Membranous Nephropathy (MN) in 13.6%, Minimal Change Disease (MCD) in 11.4%, 9.1% Diffuse Proliferative Glomerulonephritis (DPGN), 3.4%, Membranous Proliferative Glomerulonephritis (MPGN) in which one was HBsAg positive, 1.1% PSGN,and 1.1% C3 glomerulopathy. Hypertension (HTN) was found in 26%, renal impairment in 28%, hematuria in 16% anemia and oedema in 12%, and 30 % respectively. Conclusion: According to this study, IgA Nephropathy was the commonest cause 22.7% of Glomerulonephritis among total patients enrolled, whereas lupus nephritis was the second commonest 19.3% followed by focal segmental glomerulonephritis 18.1% and Membranous Nephropathy in 13.6%.